Arc-produced short-length multi-walled carbon nanotubes as “millstones” for the preparation of graphene-like nanoplatelets; Carbon; Vol. 146 - Kostoglou N. Nikolaos; Ryzhkov V. A. Vladislav Andreevich; Walters I. Ian; Doumanidis C. C. Charalabos; Rebholz C. Claus; Mitterer C. Christian (2019, 2019)
Title screen